Compressibility and Strength of Clay Subgrade of Railroad Foundation in Highly Saturated Condition - Loh, Richard; Nikraz, Hamid (Taiwan Geotechnical Society, 2012)
The aligning of railroad crossing lowland of high plasticity clay formation soil may at times become necessary despite it being technically undesirable. This has called for better understanding and extra engineering consideration / measures in the design of railroad foundation with respect to the subgrade strength capacity. This paper describes the laboratory investigation into the effect of cyclic loading produced by contemporary train on the compressibility and strength deterioration of clay subgrade in general, and kaolinite clay in particular. Concept of the lower-bound stability threshold stress is proposed for the characterization of clay sub grade and other fine-grained soil of potential high saturation, in place of the traditional tests and performance standard being used. In conjunction with this, the paper presents the theoretical model which is capable of predicting the lower-bound threshold stress of clay soil based on either the known consolidated state and stress history or the in-situ compacted state, from the fundamental soil properties obtainable in basic testing. Thereby eliminate the need for frequent lengthy testing and cyclic loading laboratory capability.